2015
DOI: 10.5935/0103-5053.20150345
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a New Spectrophotometric Method for the Determination of Cephalexin Monohydrate in Pure Form and Pharmaceutical Formulations

Abstract: A simple, fast, sensitive and accurate spectrophotometric method has been developed for the quantitative determination of cephalexin monohydrate in dosage form and in commercial formulations. The method involves the addition of Ce IV to cephalexin in acidic medium, followed by the determination of residual Ce IV by reacting with a fixed amount of methyl orange, and the absorbance was measured at 510 nm. Beer's law was obeyed in the concentration range of 0.6-20 µg mL -1 with correlation coefficient of 0.992. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Whereas, the percentage recoveries were found to be 99.48 ± 0.4%, 99.67 ± 0.6%, and 99.18 ± 0.8% for the three drugs in the presence of MnO 2 NPs, respectively. All results were statistically assessed using Student’s t -test and variance ratio F-test [ 68 ] and compared with those obtained from previously reported methods [ 69 , 70 , 71 ]. It was observed that the high sensitivity of the proposed spectrophotometric method for the determination of LVX, CPX, and CTX in the presence of NiONPs and MnO 2 NPs can be attributed to the catalytic properties of these nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the percentage recoveries were found to be 99.48 ± 0.4%, 99.67 ± 0.6%, and 99.18 ± 0.8% for the three drugs in the presence of MnO 2 NPs, respectively. All results were statistically assessed using Student’s t -test and variance ratio F-test [ 68 ] and compared with those obtained from previously reported methods [ 69 , 70 , 71 ]. It was observed that the high sensitivity of the proposed spectrophotometric method for the determination of LVX, CPX, and CTX in the presence of NiONPs and MnO 2 NPs can be attributed to the catalytic properties of these nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Belongs to published papers, more than one chromatographic approach as HPLC [2][3][4][5][6][7] and LC-Mass [8][9][10][11][12][13][14][15][16][17][18][19] also microbiological articles were reported [20,21]. On the other hand, spectroscopic techniques were listed, including spectrophotometric [22][23][24][25] and spectrofluorimetric [26][27][28] approaches. Owing to its simplicity, sensitivity, and no need for a complex apparatus or sample preparation, the spectrofluorimetry technique is frequently employed in recent drug analyses.…”
Section: Introductionmentioning
confidence: 99%
“…AT undergoes little or no metabolism in the liver and is mainly excreted in urine (over 85% of the absorbed drug is excreted in urine as unchanged drug) [1]. Different analytical techniques have been reported for the analysis of AT such as high performance liquid chromatography (HPLC) [2][3][4], spectrophotometric [2,5,6], capillary electrophoresis [7,8], gas chromatography (GC) [9], and spectrofluorimetric [10] methods. Paracetamol (PR) or acetaminophen (Figure 1(b)) is an over-the-counter (OTC) analgesic and antipyretic drug.…”
Section: Introductionmentioning
confidence: 99%